Evaluating the Performance of an Arduino-Based Strain Sensor System in a Cantilever Beam using Plastic Ruler Under Load Conditions - Amran, Nur Amirah; Ali, Ahmad Hadi (Enhanced Knowledge in Sciences and Technology, 2025)
Strain measurements are important for assessing the structural integrity of engineering systems, especially in detecting potential failures and planning maintenance strategies. Traditional strain measurement methods, however, are frequently costly and complicated, which restricts their use in small-scale and educational settings. This study focuses on the development and evaluation of an Arduino-based strain sensor system for cantilever beam testing using a plastic ruler as a test sample. The system integrates a strain gauge module, an LCD for real-time data display, and a buzzer and LED to provide feedback based on preset thresholds. The performance of the system was evaluated under various load conditions to determine its reliability and accuracy in measuring strain. Experimental results show a strong correlation with theoretical predictions, confirming the potential of the system for practical applications in structural health monitoring. This low-cost and user-friendly approach provides an effective tool for educational purposes, enabling direct exploration of strain distribution and bending mechanics.